Trends in the surgical management of vesicoureteral reflux in Finland in 2004-2014 - Ripatti Liisi; Viljamaa Hanna-Reeta; Kauko Tommi; Kytö Ville; Rautava Päivi; Sipilä Jussi; Pakkasjärvi Niklas (United Kingdom, 2022)
Objectives: Previous data on the trends of surgical treatment of vesicoureteral reflux outside USA are
scarce. The aim of this study was to clarify the national trends of operative treatment of vesicoureteral
reflux (VUR) in Finland.
Methods: We analyzed national data from Finnish Care Register for Health Care on children (<16 years
of age) surgically treated for VUR in 2004–2014.
Results: Endoscopic injections of the ureteral orifices were primarily performed for 1212 and open
ureteral reimplantation for 272 children. The use of both types of surgery decreased during the study
period (p=0.0043 and p<0.001, respectively). The median age at surgery for VUR was lower in those
treated with open ureteral reimplantation than those with endoscopic injections of the ureteral orifices
[3 and 4 years, respectively] (p=0.0001). The length of hospital stay was significantly longer (median
9.9 days) with open ureteral reimplantation compared to that (median 1.3 days) with endoscopic injections
(p<0.0001) and did not change during the study period. Reoperations were significantly more
common in patients who were primarily treated with endoscopic injections (n=146/1072, 14%) than
with ureteral reimplantation (n=7/230, 3%) (p<0.0001).
Conclusions: While the best treatment options for VUR remain debatable, operative treatment of VUR
has become less common in Finland.